(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article discusses the importance of modern computer technologies in the process of diagnosing and treating gastritis. The roles of advanced technologies such as Artificial Intelligence (AI), Machine Learning (ML), bioinformatics, big data analysis, medical image processing, and telemedicine are analyzed. The paper also explores the advantages, limitations, and future development prospects of these technologies.